Patient’s Preferences in Selecting Prosthodontist Based on Age and Sex in a Tertiary Hospital in Kathmandu - Guragain, Manjeev; Dahal, Sirjana; Joshi, Kalit R; Rathi, Ankita; Dahal, Samarika; Poudel, Samikshya S; Pantha, Sandesh; Bhochhibhoya, Amar (Journal of Institute of Medicine Nepal, 2022)
Introduction: Most of the dental research has focused on dentist’s perceptions of patients based on their demographic profiles, while little is known about patient’s perceptions of their dentists. Further, there is a lack of data regarding patient preferences in selecting prosthodontists based on gender and age in Nepal. This study aims to investigate the influence of various demographic factors on patient preferences in selecting their prosthodontist. Methods: A sample of 358 patients presenting at the Department of Prosthodontics, Tribhuvan University Teaching Hospital, Institute of Medicine for replacement of missing teeth took part in this questionnaire-based study. The questionnaire was designed to assess the influence of sex and age of the prosthodontist on the decision to select a prosthodontist. Statistical analysis was performed by SPSS version 16. Results: Majority (258, 72.1%) preferred treatment by a prosthodontist of age <44 years. There was a significant association seen between participants’ age, sex, and educational status and age preference for prosthodontists. Also, their sex, educational status, and prosthodontist among family and friends were significantly associated with prosthodontist’s sex preference. Conclusion: There was preference for younger prosthodontists by the study participants but they had no gender preference for having their treatment done.